Unstable properties Aboriginal title and the claim of British Columbia - Wood, Patricia 1968-; Rossiter, David (UBC Press, 2022)
"The so-called land question dominates political discourse in British Columbia. Unstable Properties reverses the usual approach - investigating Aboriginal claims to Crown land - to reframe the issue as a history of Crown attempts to solidify claims to Indigenous territory. From the historical-geographic processes through which the BC polity became entrenched in its present territory to key events of the twenty-first century, the authors highlight the unstable ideological foundation of land and title arrangements. In the process, they demonstrate that only by understanding diverse interpretations of sovereignty, governance, territory, and property can we move toward meaningful reconciliation."--
Includes bibliographical references and index
Keywords: Geschichte; Anspruch; Grundeigentum; Indigenes Volk; British Columbia; Indigenous peoples / Land tenure / British Columbia / History; Indigenous peoples / British Columbia / Government relations / History; Land tenure / British Columbia / History; Land tenure / Political aspects / British Columbia / History; Indigenous title / British Columbia / History; Indigenous peoples / Government relations; Indigenous peoples / Land tenure; Land tenure; Land tenure / Political aspects; History